(3OQQ GdLeGf aj OhdI ehdGfG GdSdWGf YKeGfs - (3eMeO Hf eMeO GdHcQj GdUOjbi GdeYQha HGHf CHi GdSQhQ GdHcQi,J (B1087 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdTQY HGdOhdI GdTQjaI GdYKeGfjI s
(3BNQgG (B:s
(3Ke hdi ehdGfG GdhRjQ MSjf HGTG acGf ESJjdGFg Ydi JNfJ eUQ ai jhe GdCQHYGA (B27 (3QeVGf SfI (B1029 s
(3jdi Pdc QSGdI (B: (3ai GdYQhV hGdbhGais
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B62 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B290s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B59 s
Keywords: (3GdJGQjNs